PENGARUH PEMBERIAN PAKAN TAMBAHAN SUPLEMENTASI AZOLLA (Azolla microphylla) DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Mochammad Ardan Azhar; Sri Mulatsih; Ninik Umi Hartanti (Universitas Pancasakti Tegal, 2024)
Tilapia (Oreochromis niloticus) It is one of the freshwater fish that has received considerable attention from the government which is expected to contribute to increased production. In doing fish farming business, it is hoped that fish can grow faster. One effort to accelerate the growth of Tilapia (Oreochromis niloticus) by adding supplementation to the feed. One of the supplementations that can be used Azolla. addition of Azolla supplementation (Azolla microphylla) can affect the process of growth and development of Tilapia (Oreochromis niloticus). Knowing the effect of dosing Azolla (Azolla microphylla) which is effective against the growth of Tilapia (Oreochromis niloticus). The method used in the study was an experimental method of 3 treatments using Complete Random Design (RAL), each treatment had 3 repetitions, each of which consisted of 10 TilapiaS (Oreochromis niloticus). The fish to be used in this study are Tilapia (Oreochromis niloticus) fry with a length of between 5-7 cm. As an additional feeding treatment Azolla (Azolla microphylla) supplementation with treatment doses A (20 gr), B (30 gr), C (40 gr) and control (0 cm). The results showed that each treatment differed markedly on growth and survival rates. Treatment C is the best treatment at growth of 8.9 g and daily growth rate of 0.319 gr, Tilapia (Oreochromis niloticus) fry survival in A, B, C and Control is relatively stable with a survival percentage of 100%. Water quality during the study was within a decent range for Tilapia (Oreochromis niloticus) life.